2022
DOI: 10.1186/s12935-022-02480-7
|View full text |Cite
|
Sign up to set email alerts
|

As a prognostic biomarker of clear cell renal cell carcinoma RUFY4 predicts immunotherapy responsiveness in a PDL1-related manner

Abstract: Background Clear cell renal cell carcinoma (ccRCC) is one of the most lethal malignancies in the urinary system and the existing immunotherapy has not achieved satisfactory outcomes. Therefore, this study aims at establishing a novel gene signature for immune infiltration and clinical outcome (overall survival and immunotherapy responsiveness) in ccRCC patients. Methods Based on RNA sequencing data and clinical information in The Cancer Genome Atla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…The risk score model included five genes (RGS8, RUFY4, HLA‐DQB2, THEMIS, and TRBV12‐5), and the role of RGS8 has previously been found to be controversial in solid cancers for its positive prognosis effect on thyroid carcinoma and negative prognosis effect on ovarian cancer, 43,44 while we found RGS8 high expression was associated with poor prognosis. Miao et al indicated that the depletion of RUFY4 led to the decrease of PD‐L1, speculating that RUFY4 regulated the expression level of PD‐L1 by involving in JAK–STAT and/or NF‐kappa B signaling pathways, there by influencing immunotherapy responsiveness 45 . Being a member of the MHC class II family, HLA‐DQB2 is an important molecule involved in the T cell immune response and antigen presentation.…”
Section: Discussionmentioning
confidence: 99%
“…The risk score model included five genes (RGS8, RUFY4, HLA‐DQB2, THEMIS, and TRBV12‐5), and the role of RGS8 has previously been found to be controversial in solid cancers for its positive prognosis effect on thyroid carcinoma and negative prognosis effect on ovarian cancer, 43,44 while we found RGS8 high expression was associated with poor prognosis. Miao et al indicated that the depletion of RUFY4 led to the decrease of PD‐L1, speculating that RUFY4 regulated the expression level of PD‐L1 by involving in JAK–STAT and/or NF‐kappa B signaling pathways, there by influencing immunotherapy responsiveness 45 . Being a member of the MHC class II family, HLA‐DQB2 is an important molecule involved in the T cell immune response and antigen presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Carril ajuria l et al found that the SWI/SNF chromatin remodelling complex gene PBRM1 is also one of the key genes of ccRCC [26,27]. Recent studies have found that OIP5[28], RUFY4 [29] and MUC20 [30] are related to the immune microenvironment (TME) of ccRCC and may be used as new therapeutic targets. However, these are not enough to understand the development and prognosis of ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure was carried out as previously described [ 30 ]. Cells were starved for 24 h. The top chamber of the Transwell plate (#REF3422, Corning Inc., Corning, NY, USA) was coated by the Matrigel (#356234, dilution 1:8, Corning Inc.).…”
Section: Methodsmentioning
confidence: 99%